PENGEMBANGAN MEDIA VIDEO ANIMASI TEMATIK UNTUK PENGEMBANGAN ASPEK KOGNITIF ANAK USIA 5-6 TAHUN - Masneno, Kristantri; Miranda, Dian; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2023)
This study aims to develop animated video media for the development of cognitive aspects of children aged 5-6 years. This animated video media is expected to be feasible and make it easier for children to develop their cognitive aspects. The research conducted is a type of research and development or research and development (RD) using the ADDIE method (analysis, design, development and implementation, evaluation). The study population was children aged 5-6 years in a limited scale trial with a total of 5 children and a large scale trial with a total of 13 children. Data was collected by observation for needs analysis, questionnaire distribution and validation by validators, namely material experts and media experts. The results of the study obtained an average total score of 85% for material experts and 82.6% for media experts in the